Design and Build Audio and Video Streaming on Raspberry Pi-based Reconnaissance Robot for Android - Anisah Meidella; Irma Salamah; R.A Halimatuss’adiyah (Politeknik Piksi Ganesha Indonesia, 2021)
The development of sophisticated technology for human life starts from the development of computerized technology, information and communication technology, and technology in the field of mechanics, especially robotics. Robotics technology is a form of technological change that creates innovations all the time. The purpose of this design was to implement the technology concept of the Raspberry Pi microcontroller in the form of military applications, household chores, industrial areas monitoring, and security maintenance that may cause high dangerous risks without the user going directly to carry out the activities. The method used in developing the concept of merging audio and video followed the MJPEG Streamer and Darkice method. The product was a robot that resembles a car made using wheels that moves in the direction the user wants via an Android control. The communication employs a Raspberry Pi server sent from the robot to Android by displaying a streaming screen on the application. The data obtained are in images and sounds generated from the camera on the robot.